Tema e significação: contribuições bakhtinianas para análise crítica dos processos interativos em aulas de leitura de textos shakespeareanos (Revista de Estudos da Linguagem, 2004)
This article discusses interactive processes in the reading andpresentation of Shakespearean plays in public schools of poorneighborhoods in the outskirts of Belo Horizonte. The originalproject had as its main aims the dialogue of languages and culturesand the search for a “non-traditional” teaching practice, a practicewhich would involve conscientization and polyphony.Starting with reflections from Bakhtin’s conceptions of theme andsignification, and trying to go beyond them, we bring out therelevance of contextual understanding as well as the debate ofideological questions in the classroom, a place where the subjectconstitutes him/herself and is constituted by the “others”.– Que pão!Doce? De mel? De açúcar? De ló? De ló de mico? De trigo?De milho? De mistura? De rapa? De saruga? De soborralho?Do céu? Dos anjos? Brasileiro? Francês? Italiano? Alemão? DoChile? De forma? De bugio? De porco? De galinha? Depássaros? De minuto? Ázimo? Bento? Branco? Dormido? Duro?Sabido? Saloio? Seco? Segundo? Nosso de cada dia? Ganhocom o suor do rosto? Que o diabo amassou?A eterna imprecisão da LinguagemCarlos Drummond de Andrade